Utero-tubal insufflation in normal cycles and induced - Bunster, Eduardo (2015)
The authors performed 107 breaths quimográficas women carrying normal tubes in the four weeks of the menstrual cycle in 30 postmenopausal women and in two cases of ovarian agenesis. In normal women find that both the initial úterotubaria tone as the average of the voltages passes gas during insufflation are lower in the last week of the cycle. Studying the problem in relation to the degree of maturation of the endometrium find that the initial utero-tubal tone is minimal in the initial secretory endometrium type (equivalent to the third week of the normal cycle) being high in estrogen Endometriosis. Considering the average of successive voltages during insufflation find that it is low in the mature secretory endometrium The inflations performed in 30 climacteric women show that the utero-tubal initial tone is low, that it increases if treatment is descending estrogen plus progesterone minimum figures if administered. Utero-tubal average voltage observed during the entire inflation is also lower than in younger women, ascends and descends the estrigénica therapy without progesterone to be added to the figures achieved in climacteric not treated with hormones. The results obtained in the cases of congenital ovarian failure (Ovarian agenesis) are similar to those of climacteric. Light of the facts it follows that both the initial úterotubaria quimográfica tonicity such as pressure during insufflation appear subordinate to the action of ovarian steroids. Such tensions elevated estrogen and progesterone, focussing on these last facilitates gas through the interstitial portion of the tubes. Consequently, the impermeability of the fallopian physiological assumed hypothetically that could occur with increasing pre-menstrual endometrial thickness does not exist, as evidenced also a case permeability easily observed by one of the authors in a pregnant 15 days . The authors recommend as more appropriate for the insufflation the second week of the cycle time but insist that it can properly be held in the third or fourth week whenever any possibility of pregnancy is removed.